CÂT DE COMPATIBILĂ ESTE OBLIGATIVITATEA LEGALĂ DE VACCINARE A COPIILOR CU ARTICOLUL 8 AL CONVENȚIEI EUROPENE A DREPTURILOR OMULUI? (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
How compatible is the statutory child vaccination duty with article 8 of the European Convention on Human Rights?On April 8, 2021 the Grand Chamber of the European Court of human Rights (ECtHR) adopted a first judgment on compulsory childhood vaccination. This judgment, adopted by a clear majority (sixteen votes to one) in the case of Vavřička and Others v. the Czech Republic, established that the general legal duty consecrated in Czech Republic to vaccinate children against a number of diseases well known to medical science does not violate article 8 (right to respect for private an family life) of the European Convention on Human Rights (ECHR), as requested by the applicants. In the above mentioned case, the first applicant, according to the Czech legislation, was fined for failure to respect the vaccination duty for his two children, the other applicants being all denied for the admission of their children to nursery school for the same reason. Following its constant case law in relation with article 8, the ECtHR examined the issues of the State interference in the right to respect for private life, the legitimate aims pursued by the Czech authorities in protecting health, the margin of appreciation of the State and the proportionality principle. The Court reached the conclusion that in striking the particular balance between the need to respect the right to private life and the legitimate aim to safeguard the health of young children and the community, respectively, the Czech authorities had not exceeded both the recognized margin of appreciation for a State when adopting measures regarded as ‘necessary in a democratic society” and the principle of proportionality.